2014
DOI: 10.1111/ijn.12353
|View full text |Cite
|
Sign up to set email alerts
|

Multiparous mothers: Breastfeeding support provided by nurses

Abstract: The study aimed to identify the informational, practical and emotional support that multiparous mothers had received from nurses in the early postpartum period.This is a descriptive and cross-sectional study on 278 multiparous mothers who took part in the research prior to their discharge from a maternity hospital in Ankara, Turkey. The instrument used was a 38-item questionnaire. Experiencing breastfeeding problems was the only statistically significant predictor of in-hospital supplementation (P < 0.01, OR 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 44 publications
(160 reference statements)
0
11
0
5
Order By: Relevance
“…O aleitamento materno (AM) tem forte impacto sobre a mortalidade infantil, minimizando as mortes por causas evitáveis. (Silvaet al;2014;Urbanetto et al;2018 & Gasparin et al;2019). Do ponto de vista materno, evidencia-se um estreitamento do vínculo mãe-bebê, proteção contra ao câncer de colo de útero, menores chances de desenvolver câncer de mama, e evidências científicas também sobre câncer epitelial de ovário, e ao mesmo tempo evitar morbidades maternas relacionadas à hemorragia pós-parto (Netto et al;Leal et al;2016 & Baptista et al;2015).…”
Section: Benefícios Da Amamentaçãounclassified
See 3 more Smart Citations
“…O aleitamento materno (AM) tem forte impacto sobre a mortalidade infantil, minimizando as mortes por causas evitáveis. (Silvaet al;2014;Urbanetto et al;2018 & Gasparin et al;2019). Do ponto de vista materno, evidencia-se um estreitamento do vínculo mãe-bebê, proteção contra ao câncer de colo de útero, menores chances de desenvolver câncer de mama, e evidências científicas também sobre câncer epitelial de ovário, e ao mesmo tempo evitar morbidades maternas relacionadas à hemorragia pós-parto (Netto et al;Leal et al;2016 & Baptista et al;2015).…”
Section: Benefícios Da Amamentaçãounclassified
“…Outros fatores que dificultam são as situações enfrentadas pelas mulheres, por não terem a possibilidade de demonstrar suas vontades, intenções e condições de bem-estar para o estabelecimento pleno do aleitamento materno e acabam apresentando condições de exaustão, dor, e comportamentos inesperados que podem prejudicar o curso da amamentação e que devem ser avaliados com cautela. (Castro et al, 2019) Apresentam dificuldades como a pega incorreta no peito, (Bortoli et al, 2019;Urbanetto et al, 2018& Demirtas 2014. Fissura mamilar, ingurgitamento mamário, mastite (Urbanetto et al, 2018), estes que em geral são relacionadas como fator negativo na prática da amamentação, mas podem seguramente serem minimizadas, por meio de orientações, do incentivo e encorajamento, dos ensinamentos de técnicas e das medidas profiláticas durante o pré-natal e, posteriormente, com suporte adequado principalmente no início da amamentação.…”
Section: Dificuldade Das Mães Com a Amamentaçãounclassified
See 2 more Smart Citations
“…There have been, however, very few tools created for the purpose of systematically identifying those women at risk of breastfeeding issues (Casal, Lei, Young, & Tuthill, 2017). Many of these tools rely on the importance of breastfeeding self-confidence, but few include the potential impact, if any, of prior breastfeeding experience on future efforts (Demirtas, 2015; Burns et al, 2018). One descriptive study of 180 multiparous women in the early postpartum period found that a history of breastfeeding problems with a prior infant was the only predictor of in-hospital formula supplementation (Demirtas, 2015).…”
Section: Introductionmentioning
confidence: 99%